Anti-Hyperglycemic Effect of Tecomella undulata Extract by Ameliorating Pancreatic Dysfunction in Streptozotocin Induced Diabetic Albino Rats - Trishna Das, Bhabesh Das, Dipankar Saha, Shanti Bhushan Mishra (Journal of Applied Pharmaceutical Science, 2015)
Objective: The primary objective of the present investigation is to evaluate the antihyperglycemic activity of the 50% ethanolic extract of the Tecomella undulata Seem. (TUE) bark in the streptozotocin induced diabetic rats.Methods: Single intraperitoneal injection (i.p.) of streptozotocin (60 mg/kg body weight) was used for induction of diabetes is wistar albino rats. The induction of diabetes was confirmed after 3 days after STZ injection and rats with fasting blood glucose levels greater than 200 mg/dl were considered to be diabetic used in the experiment. TUE at a once a daily dose of 250 mg/kg, and 500 mg/kg, p.o. along with glibenclamide 600µg/kg, p.o. was also given for 21 days. On the 21st day rats from all the groups fasted overnight and the blood was collected from the puncturing the retro orbit of the eye under mild ether anesthetic condition. The oral acute toxicity studies did not show any toxic effect till the dose at 2000 mg/kg. Results: The statistical data indicated that the different doses of the TUE significantly decreases the level of fasting blood glucose, total cholesterol, triglycerides, low density lipoprotein and increase high density lipoprotein in STZ induced diabetic rats. This result indicated that T. undulata extract can protect pancreatic β-cells from STZ-induced damage which is confirmed by the results of the histopathological examination of the pancreas.Conclusion: Our investigation has clearly indicated that the bark extract of Tecomella undulata Seem. showed remarkable antihyperglycemic activity due to its possible systematic effect involving in the pancreatic and extra pancreatic mechanism. Moreover, the antihyperlipidemic activity was exerted possible by lowering the higher level of lipid profile.
Keywords: Bark extract, Diabetes, Histopathology, Pancreas, Tecomella undulata.